2021
DOI: 10.3390/s21217387
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Method for Considering Achilles Tendon Curvature in the Assessment of Tendon Elongation

Abstract: The consideration of the Achilles tendon (AT) curvature is crucial for the precise determination of AT length and strain. We previously established an ultrasound-kinematic-based method to quantify the curvature, using a line of reflective foil skin markers covering the AT from origin to insertion. The current study aimed to simplify the method by reducing the number of markers while maintaining high accuracy. Eleven participants walked (1.4 m/s) and ran (2.5, 3.5 m/s) on a treadmill, and the AT curvature was q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, in this study, the free tendon was measured as a straight line, which could have affected the accuracy of the results. Kharazi et al found that Achilles tendons measured using a straight line underestimated the length by 0.1 to 4.3 mm during the walking gait cycle [ 50 ] Since this straight-line technique was used for all patients, both cases and controls, the comparison of the free tendon lengths is justifiable. There was no significant difference in tibiotalar angle between the two groups ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, the free tendon was measured as a straight line, which could have affected the accuracy of the results. Kharazi et al found that Achilles tendons measured using a straight line underestimated the length by 0.1 to 4.3 mm during the walking gait cycle [ 50 ] Since this straight-line technique was used for all patients, both cases and controls, the comparison of the free tendon lengths is justifiable. There was no significant difference in tibiotalar angle between the two groups ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%